The Influence of Bioactive Compounds in Arabica Coffee Extract on TNF- Alpha Regulation in Animal Models: A Systematic Literature Review - Rahasbistara, Made Rendra Wisnu; Yasa, I Wayan Putu Sutirta (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
Arabica coffee (Coffea arabica) contains bioactive compounds such as caffeine and chlorogenic acid, known for their anti-inflammatory potential through the regulation of tumor necrosis factor-alpha (TNF-α), a key pro-inflammatory cytokine involved in metabolic and neurodegenerative diseases. This systematic literature review aims to synthesize evidence from post-2020 studies on the effects of Arabica coffee bioactive compounds on TNF-α regulation in animal models. This review adheres to the PRISMA 2020 guidelines, including experimental studies (2021–2025) from PubMed, Scopus, Web of Science, and Google Scholar. Inclusion criteria encompassed studies using animal models, focusing on Arabica coffee bioactive compounds, and employing quantitative TNF-α measurements (ELISA, RT-PCR, Western Blot). Data were extracted on study characteristics, animal models, bioactive compounds, measurement methods, outcomes, and molecular mechanisms, with quality assessed using SYRCLE’s Risk of Bias Tool. From 900 articles, 20 met inclusion criteria after rigorous screening. Wistar rats (30%) were the dominant animal model, followed by BALB/c mice and Sprague-Dawley rats (10% each). Compounds like caffeine (6 mg/kg) and chlorogenic acid reduced TNF-α via oxidative stress modulation and NF-κB suppression. Green coffee bean extract (200 mg/kg) showed dose-dependent effects, with higher doses increasing TNF-α. ELISA (55%) was the primary measurement method. Mechanisms included antioxidant activity, inhibition of gut inflammation, and immunomodulation. Arabica coffee bioactive compounds consistently reduce TNF-α, supporting their therapeutic potential for chronic inflammation. Variability in doses and animal models underscores the need for standardized protocols to enhance clinical translation.